Some New Dynamic Inequalities Involving Monotonic Functions on Time Scales. (8th May 2019) - Saker, S. H.; Awwad, E.; Saied, A.
Abstract : In this paper, we prove some new dynamic inequalities involvingC - monotonic functions on time scales. The main results will be proved by employing Hölder's inequality, integration by parts, and a chain rule on time scales. As a special case whenT = R, our results contain the continuous inequalities proved by Heinig, Maligranda, Pečarić, Perić, and Persson and whenT = N, the results to the best of the authors' knowledge are essentially new.